The oppositional unity between careerism and critical public engagement - Alexander, Tarryn Linda (Rhodes University, 2026)
This thesis develops and offers a dialectical-relational analysis of how contemporary neoliberalisation configures the academic identities of sociologists at universities in the Eastern Cape Province of South Africa. The dissertation draws on an internal relations philosophy, particularly Bertell Ollman’s Marxist dialectic, as well as Pierre Bourdieu’s relational sociology, to identify and examine the tensions marking the academic identity of sociologists at these universities. Through the use of Marx’s method and based on an internal relations ontological commitment, the thesis identifies an underlying contradiction which characterises the neoliberalising university: between insular careerism and critical public engagement. However, it is argued that these sociologists experience and understand the tensions – in their identities and practices – in terms of paradoxes rooted in an external relations conception of the world. Sociologists provides a particularly fascinating case for studying the tensions characterising the neoliberalising university. This distinctiveness stems from the unique position they occupy, associated with an intellectual commitment to social justice and emancipation while simultaneously becoming embedded in an insular and (self-) commodifying ethos of practice. Neoliberal incursions include the heightened focus on individual competition, performance- auditing, and instrumentalisation, which distorts the principle and call to public engagement. This is a reflexive ethnographic study which employs in-depth interviews with full-time academic sociologists as the source for primary data. The academics were recruited using convenience and snowball sampling, and hail from three universities in the Eastern Cape Province. The researcher’s social positioning and experiences also shape the impetus and framing of the study, inevitably incorporating elements of self-disclosure and self-analysis. Ultimately, however, the focus is on capturing relational dynamics from the respondents’ perspectives. This study is located at the intersections of higher education research, Marxist dialectical critique, relational sociology, and reflexive ethnography to analyse the nature of contradictions in academic work and what conceptualising them more fully can mean for social change.
a reflexive ethnography of sociologists in neoliberalising universities in the Eastern Cape, South Africa
Keywords: Dialectic; Contradiction; Identity (Psychology); Neoliberalism; Public sociology; Educational anthropology; Ollman, Bertell